MicroRNA Profiling in Adipose Before and After Weight Loss Highlights the Role of miR‐223‐3p and the NLRP3 Inflammasome. Issue 3 (24th February 2020) - Macartney‐Coxson, Donia; Danielson, Kirsty; Clapham, Jane; Benton, Miles C.; Johnstone, Alice; Jones, Angela; Shaw, Odette; Hagan, Ronald D.; Hoffman, Eric P.; Hayes, Mark; Harper, Jacquie; Langston, Michael A.; et al.
Abstract : Objective: Adipose tissue plays a key role in obesity‐related metabolic dysfunction. MicroRNA (miRNA) are gene regulatory molecules involved in intercellular and inter‐organ communication. It was hypothesized that miRNA levels in adipose tissue would change after gastric bypass surgery and that this would provide insights into their role in obesity‐induced metabolic dysregulation. Methods: miRNA profiling (Affymetrix GeneChip miRNA 2.0 Array) of omental and subcutaneous adipose ( n  = 15 females) before and after gastric bypass surgery was performed. Results: One omental and thirteen subcutaneous adipose miRNAs were significantly differentially expressed after gastric bypass, including downregulation of miR‐223‐3p and its antisense relative miR‐223‐5p in both adipose tissues. mRNA levels of miR‐223‐3p targets NLRP3 and GLUT4 were decreased and increased, respectively, following gastric bypass in both adipose tissues. Significantly more NLRP3 protein was observed in omental adipose after gastric bypass ( P  = 0.02). Significant hypomethlyation of NLRP3 and hypermethylation of miR‐223 were observed in both adipose tissues after gastric bypass. In subcutaneous adipose, significant correlations were observed between both miR‐223‐3p and miR‐223‐5p and glucose and between NLRP3 mRNA and protein levels and blood lipids. Conclusions: This is the first report detailing genome‐wide miRNA profiling of omental adipose before and after gastric bypass, and it further highlights the association of miR‐223‐3p and the NLRP3 inflammasome with obesity.